El movimiento zapatista y la transición democrática en México: Oportunidades para la movilización, el éxito y la supervivencia. Una revisión. - Zamora Lomelí, Carla Beatriz (El Colegio de México, 2023)
The book review of the book El movimiento zapatista y la transición democrática en México: Oportunidades para la movilización, el éxito y la supervivencia (Inclán, 2021) is presented, which deals with the analysis of the structure of political opportunities for the insurgent indigenous movement based in the state of Chiapas, and how the closing of opportunities occurred to obtain the success of the political demands referred to the constitutional reform in terms of indigenous rights and culture. From the conclusion that points to the closing of political opportunities and the tendency of the movement towards the transnational solidarity network, new lines of research and questions that the text opens are visualized.